Sugar Palm (Arenga Pinnata (Wurmb.) Merr) Cellulosic Fibre Hierarchy: A Comprehensive Approach From Macro To Nano Scale - Mohd Sapuan, Salit; Ilyas, Rushdan Ahmad; Jumaidin, Ridhwan; Shaharuzaman, Mohd Adrinata; Ibrahim, Rushdan; Abral, Hairul; Ishak, M.R.; Zainudin, E.S.; Asrofi, Mochamad; Mahmud, Siti Nur Atikah; Muhammad Huzaifah, Muhammad Roslim; Mohd Radzi, Ali; et al. (Elsevier B.V, 2019)
Sugar palm (Arenga pinnata) fibre is considered as a waste product of the agricultural industry. This paper is investigating the isolation of nanofibrillated cellulose from sugar palm fibres produced by a chemo-mechanical approach, thus opening a new way to utilize waste products more efficiently. Chemical pre-treatments, namely delignification and mercerization processes, were initially involved to extract the sugar palm cellulose. Then, mechanical pre-treatment was performed by passing the sugar palm cellulose through a refiner to avoid clogging in the subsequent process of high pressurized homogenization. Nanofibrillated cellulose was then characterized by its chemical properties (Fourier transform infrared spectroscopy), physical morphological properties (i.e. scanning electron microscopy, transmission electron microscopy, X-ray diffraction analysis), and thermogravimetric analysis.The nanofibres were attained at 500 bar for 15 cycles with 92% yield. The results showed that the average diameter and length of the nanofibrillated cellulose were found to be 5.5 ± 1.0nm and several micrometres, respectively. They also displayed higher crystallinity (81.2%) and thermal stability compared to raw fibres, which served its purpose as an effective reinforcing material for use as bio-nanocomposites. The nanocellulose developed promises to be a very versatile material by having a huge potential in many applications, encompassing bio-packaging to scaffolds for tissue regeneration